Dasawarsa: Kinerja Lingkungan terhadap Nilai Perusahaan - Harsono, Edi; Said, Darwis; Indrijawati, Aini (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The most basic purpose of establishing a company is to make a profit. The development of management understanding encourages the postponement of current income or expense to expect sustainability in the future or better earnings in the next period. Although the view of the Single Bottom Line has begun to be corrected by experts since the arrival of the Triple Bottom Line, the regulations governing it are not yet available. Through directed and continuous research, accounting standards that regulate the presentation of environmental-based reports will be taken on board soon. This article aims to collect and put together to provide a broader picture. The method used in this research is a systematic literature review. The presentation of this article is sunder into Introduction, Research Methodology, Results of Literature Review, Discussion and Discussion, and Conclusions, Limitations, and Suggestions. This article produces variations in the relationship between different variables. The inference presented by this article gives an opening to further research opportunities.